Antimicrobial activity of Salvia spinosa against Enterococcus faecalis causing endodontic infections: an in-vitro, ex-vivo, and in-silico study - Wedad M. Nageeb; Sherouk Hussein Adam; Nihal Ali; Marwa Sharaan (BMC Complementary Medicine and Therapies)
Abstract Background Enterococcus faecalis (E. faecalis) often persists in root canal systems and it is rather unsusceptible to many root canal medications including the standard Calcium Hydroxide treatment which often causes therapeutic failure. Natural herbal alternatives are preferred as new intracanal medications since they are less-toxic, renewable, and are cost-effective. The aim of this work was to assess the effectiveness of Salvia spinosa and its combination with Calcium Hydroxide as intracanal medications for eliminating Enterococcus faecalis in an ex-vivo root canal infection model compared to standard Calcium Hydroxide treatment. Methods Salvia spinosa methanolic extract was tested using the standard disc diffusion method against Enterococcus faecalis ATCC 19433 and compared to Ca(OH)2 and their combination. Forty-four extracted teeth were divided into 3 experimental groups and a control group. An ex-vivo model of endodontic teeth infection was established to test the effect of S. spinosa and its combination with Ca(OH)2. against E. faecalis. Further in-silico testing of the interaction of 19 S. spinosa active constituent with 9 important E. faecalis surface adhesins and virulence proteins was performed using Autodock tools. Results S. spinosa extract and its combination with Ca(OH)2 possess similar antibacterial effects which were significantly higher than conventional Ca(OH)2. Flavone, Flavonone, Spathulenol, and Caryophyllene oxide are the best of the tested binding active substances of S. spinosa to most of the Enterococcal surface proteins studied. Both Enterococcal surface protein (6ORI) and the collagen adhesion protein (2Z1P) could act as important E. faecalis drug targets. Conclusion S. spinosa shows promising antimicrobial activity against E. faecalis and thus offers a promising natural alternative approach to treat root canal endodontic infections for further detailed testing and investigation.